Education and science: current trends - Savotkin N. A., Pashkevich O. I., Alisin V. V., Litvinskiy V. M., Morev A. V., Lysenko E. M., Korotenko S. V., Mishina E. V., Kozikhina M. V., Lezina T. V., Kolotygina E. A., Nadtochii I. B., Zernii I. V., Bakhmisova M. A., Tolmacheva N. A., Kuzovova N. L., Tolstova O. S., Variushchenko V. I., Gaikova O. V. (Education and science: current trends, 2019)
in the article from the position of acmesynergetic and socio-cultural approaches with the help of general theoretical methods of research of pedagogical problems and included monitoring of the processes of socialization, acculturation and acmeologization of university students the key concepts of formation of the culture of life of students in the educational space of higher education were developed and justified.
Keywords: образовательное пространство; культура жизни; поликультурный образовательный процесс; принцип культуросообразности; культура бытия; векторы культуры жизни; концепты; culture of life; multicultural educational process; principle of cultural diversity; culture of being; educational space; vectors of culture of life; concepts